Design Of a Web-Based Library Book Borrowing and Return Information System - Cindy Chintya Aulia Telaumbanua; Juliandri Juliandri (Journal of Technology Informatics and Engineering, 2024)
The SMP N 1 Pantai Cermin library has a manual book loan and return system by recording in a ledger so that researchers build a website-based book loan and return application. The purpose of this research is to facilitate data collection and monitoring of borrowing and returning books at the SMP N 1 Pantai Cermin library. The results of the research are applications that help the SMP N 1 Pantai Cermin library admin in recording book loans and returns and having a digital loan report.